Yogyakarta Team Management Evaluation - Giofandi Samin; Gilang Ramadan; Arief Ibnu Haryanto; Iwan Fataha; Sulasikin Sahdi Kadir; Ardin Abdul Gani (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
This study aims to evaluate the 2017 PORDA activity coaching program in Yogyakarta City. This study uses program evaluation research which consists of a context evaluation approach, input, process, product. The sample in this study used purposive sampling with criteria considered to know best about what is expected, which then determined the number of 21 people. The results of this study are that: The context evaluation approach has a good category. The input evaluation approach has a good class. The process evaluation approach has a reasonable level. The product evaluation approach has a week category. Meanwhile, the overall analysis of the context, input, process, and product management evaluation is a good category.